Progress and perspectives on halide lithium conductors for all-solid-state lithium batteries - Li, Xiaona; Liang, Jianwen; Yang, Xiaofei; Adair, Keegan R; Wang, Changhong; Zhao, Feipeng; Sun, Xueliang (Energy & environmental science, 2020)
Halide solid-state electrolytes (SSEs) with high room-temperature ionic conductivity (>10 −3 S cm −1 ), wide electrochemical windows, and good compatibility toward oxide cathode materials have achieved impressive progress and attracted significant attention for application in all-solid-state lithium batteries (ASSLBs). This review presents an overview of halide SSEs, including their development, structure, ionic conductivity, chemical stability, and current limitations. Firstly, we give a brief overview of the historical development of halide-based SSEs, followed by an introduction to the different types of halide SSEs. From a practical point of view, the synthesis methods, especially scalable liquid-phase synthesis, are intensively discussed. Then, the associated stability issues involving basic structure stability, air/humidity stability, and electrochemical stability (electrolyte/SSE interface and electrochemical stability window) are also discussed in detail. Comprehensive coverage and thorough understanding of the properties of halide SSEs are provided and it is expected to help guide the development of future SSEs towards ASSLBs for energy storage applications. This review focuses on fundamental understanding, various synthesis routes, chemical/electrochemical stability of halide-based lithium superionic conductors, and their potential applications in energy storage as well as related challenges.